Egyenlő munkáért egyenlőtlen bér – avagy mennyire értékteremtő a közfoglalkoztatási bér? - Sipos, Marcell (Debreceni Jogi Műhely, 2019)
The aim of this paper is to scrutinise the wages in the Hungarian public work programme – probably the most controversial anomaly of the Act CVI of 2011 on public work and the modification of the act on public work and other acts. Furthermore, the study analyses the effectivity of the value creation in this programme and exposes the passive sight of the public work.The paper identifies the public work programme as a hybrid contract of the Hungarian labour law and detected the social side of this kind of legal instrument of the active labour market policies. The research also focuses on Order no. 3175/2016 of the Hungarian Constitutional Court and highlights the discriminative dangers of the wages. To emphasize my opinion I set the European Pillar of Social Rights in the middle of the research and concluded that the national regulation is not even enough to create effective reintegration to the primal labour market. In my opinion, to increase the effectivity of this program, we need to use the principles of the Social Pillar and the national labour law system. The conclusion of the paper can be a possible way to highlight the value creation in the public work programme.